Two for the price of one: emerging carbapenemases in a returning traveller to New York City. (18th July 2018) - Mittal, Jaimie; Szymczak, Wendy A; Guo, Yi; Levi, Michael H; Chen, Liang; Kreiswirth, Barry N; Riska, Paul F; Nori, Priya
Abstract : We report a case of a complex orthopaedic infection in a patient returning to New York City from Bangladesh where he was involved in a serious motor vehicle accident. He developed extensive osteomyelitis with a carbapenem-resistant Klebsiella pneumoniae . The isolate was unique due to the coexistence of New Delhi metallo-β-lactamase-1 and Oxacillinase type-181 carbapenemases, which are relatively uncommon in North America and were presumably acquired in Bangladesh. Herein, we explore challenges associated with management of carbapenem-resistant Enterobacteriaceae infections, including limited available data on effective antimicrobial therapy. We also highlight the added value of rapid diagnostic technology in guiding clinical management. Ultimately, the patient required both aggressive surgical management and combination therapy with aztreonam and ceftazidime-avibactam for true source control and favourable clinical outcome.